The Politics of Technological Change in Prussia : Out of the Shadow of Antiquity, 1809-1848. - Brose, Eric Dorn (Princeton legacy library., 2014)
Throughout the 1800s the process of industrialization contributed to painful social upheaval and wrenching political readjustments in the Kingdom of Prussia, traditionally viewed as Europe's great, modernizing, economic leader. This book illuminates the early years of this transition by examining the contradictory economic policies adopted by the state after Prussia's defeat by Napoleon. A fascinating history of modernization emerges as Eric Dorn Brose explores competing visions among soldiers, businessmen, and bureaucrats, who, largely influenced by the ideals of classical antiquity, conce.